2013
DOI: 10.1002/emmm.201201823
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics identifies five distinct molecular subtypes with clinical relevance and pathways for growth control in epithelial ovarian cancer

Abstract: Epithelial ovarian cancer (EOC) is hallmarked by a high degree of heterogeneity. To address this heterogeneity, a classification scheme was developed based on gene expression patterns of 1538 tumours. Five, biologically distinct subgroups — Epi-A, Epi-B, Mes, Stem-A and Stem-B — exhibited significantly distinct clinicopathological characteristics, deregulated pathways and patient prognoses, and were validated using independent datasets. To identify subtype-specific molecular targets, ovarian cancer cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
255
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 207 publications
(267 citation statements)
references
References 80 publications
7
255
0
Order By: Relevance
“…S4A). TGFb gene expression signature (126 genes) and EMT scoring methods (254 genes), described earlier were utilized to compare expression signatures (24)(25)(26). As expected, TGFb-treated samples showed higher enrichment for TGFb signature (0.14 for control vs. 0.84 after TGFb, Ã , P < 0.05), validating the Bioinformatic scoring (Fig.…”
Section: Hmox1 Downregulation In Runx3-inactivated Cellssupporting
confidence: 71%
“…S4A). TGFb gene expression signature (126 genes) and EMT scoring methods (254 genes), described earlier were utilized to compare expression signatures (24)(25)(26). As expected, TGFb-treated samples showed higher enrichment for TGFb signature (0.14 for control vs. 0.84 after TGFb, Ã , P < 0.05), validating the Bioinformatic scoring (Fig.…”
Section: Hmox1 Downregulation In Runx3-inactivated Cellssupporting
confidence: 71%
“…Finally, we also compared ScreenBEAM with MAGeCK and HitSelect on two other NGS-based FG screens (Qin et al, 2014;Tan et al, 2013), which had massive individual validations of identified hits. We compared the false discovery rates of validated positive hits scored by the three algorithms.…”
Section: Ngs-based Data: Screenbeam Robustly Outperforms Mageck and Hmentioning
confidence: 99%
“…1C). OVCAR-5 has characteristics of high-grade serous carcinoma (Anglesio et al 2013, Mitra et al 2015, and SKOV-3 cells are atypical nonserous carcinoma cells with mesenchymal characteristics (Anglesio et al 2013, Tan et al 2013. Further studies are required to confirm whether the co-culture findings are generalisable to other ovarian cancer subtypes.…”
Section: Introductionmentioning
confidence: 98%